PENGARUH MEDIA AUDIO VISUAL DAN DEMONSTRASI LANGSUNG TERHADAP HASIL TENDANGAN LURUS PADA UKM TAPAK SUCI UNIVERSITAS LAMPUNG - Riza Fahmi Al Faqih; Suranto Suranto; Surisman Surisman; Akor Sitepu (Journal Physical Education, Health and Recreation, 2018)
The problem of this researchis the ability of straight kick in UKM Tapak Suci University of Lampung has not reached the maximum level. This research aims to determine the difference in influence by giving some treatments, those were an audiovisual model exercise and direct demonstration. This research used pure experiment with sample of 30 people. The data collection technique used straight kick skill instruments and the data analysis was using t test technique. The result showed that tvalue= - 3.718≤ - t table= - 2,048 therefore H0n rejected and H3 accepted. There was significant difference in using audio visual and direct demonstration to the results of straight kick in UKM Tapak Suci University of Lampung. The result of this research indicated that direct demonstration provided a better influence in improving the ability of straight kick compared to the practice of audio visual media in UKM Tapak Suci University of Lampung.